Diseño del centro de exhibiciones “Mindalae' interconectado hacia la Plaza de Ponchos mediante un eje urbano a lo largo de la calle Quiroga para la ciudad de Otavalo - Martínez Cuestas, Marjorie Lilibeth (2023)
Otavalo is the intercultural capital of Ecuador, standing out worldwide for its cultural richness. The city is visited by both national and international tourists, being the poncho square its iconic place, recognized in various parts of the world. Once a week, the streets around the square are pedestrianized and become part of the fair. The streets surrounding the Plaza de Ponchos have been converted into pedestrian fairs for several years due to the great commercial activity that takes place in and around the plaza. However, this increase in commercial activity has also generated disorder and a large pedestrian flow, and at the end of this street, there are public spaces and green areas in a state of abandonment, including a fragment of the 'El Tejar' creek that has been the subject of conflicts. It can be clearly noted that in this area, there are great contrasts in terms of the use of public space, as some places are overused, while others are completely abandoned. A strategic solution is needed to address the problems in the poncho plaza and along the Quiroga road. This solution would include concepts such as pedestrianization of streets, tactical urbanism and rehabilitation of abandoned green spaces. In addition, it seeks to create an architectural facility that meets the needs of the different users and activities in the sector. The design proposes both urban and architectural solutions that address all the axes analyzed in the project. Cultural, touristic and commercial aspects are considered for the development of the city, and the conditions of the public spaces near the poncho square are evaluated in order to find solutions to the disorganized urban image.